Design and test of an adaptive self-excited/forced mode intelligent vibrating subsoiler - Guo, Mingzhuo; Yang, Wen; Zhang, Chengliang; Sun, Xiaosong; Zhao, Junxiang; Wang, Baofeng; Lan, Tianyi; Feng, Guohui; Zhao, Jiale (International Journal of Agricultural and Biological Engineering, 2025)
Subsoiling is an effective tillage technique for alleviating soil compaction, but the high traction resistance encountered at deeper working depths constrains its widespread application. To address this issue, a self-excited and forced intelligent vibrating subsoiler was developed. The subsoiler is equipped with a compound vibration mechanism that can adaptively switch between self-excited vibration and forced vibration modes based on real-time monitoring of soil resistance. Field experiments were conducted to evaluate the performance of the self-excited and forced vibrating subsoiling (SEFV). These experiments compared its performance with conventional subsoiling (CS) and self-excited vibrating subsoiling (SEV) at different working depths (35-45 cm) and forward speeds (2 and 4 km/h). The results showed that at 2 km/h, SEFV operated in self-excited vibration mode and reduced traction resistance by 12.4%-13.1% compared to CS, with no significant difference from SEV. At 4 km/h, the resistance reduction effect of SEFV became more pronounced with increasing depth. At 45 cm depth, SEFV reduced traction resistance by 9.9% and 18.9% compared to SEV and CS, respectively, as it switched to forced vibration mode to overcome the high soil resistance. SEFV also maintained high subsoiling depth stability (>90%) at both speeds and all depths tested, demonstrating its advantage over SEV under high resistance conditions. The intelligent control system based on resistance feedback enabled the SEFV to automatically adapt to variable soil conditions and optimize its vibration behavior for improved subsoiling performance and energy efficiency. This study provides new insights into the design of adaptive vibrating subsoilers for enhanced tillage operations. Keywords: vibrating subsoiler, self-excited vibration, forced vibration, adaptive control, vibration mode switching DOI: 10.25165/j.ijabe.20251804.9420Citation: Guo M Z, Yang W, Zhang C L, Sun X S, Zhao J X, Wang B F, et al. Design and test of an adaptive selfexcited/forced mode intelligent vibrating subsoiler. Int J Agric & Biol Eng, 2025; 18(4): 101–109.